2013
DOI: 10.1186/1756-3305-6-164
|View full text |Cite
|
Sign up to set email alerts
|

Leishmaniasis sand fly vector density reduction is less marked in destitute housing after insecticide thermal fogging

Abstract: BackgroundInsecticide thermal fogging (ITF) is a tool to control vector borne diseases. Insecticide application success for vector control has been associated with housing materials and architecture. Vector abundance is correlated with weather changes. Nevertheless, housing quality and weather impacts on vector abundance have been unaccounted for in most New World insecticide control trials for leishmaniasis vectors.MethodsWe conducted a 15 month insecticide control trial that included two deltamethrin [6 mg a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
54
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 61 publications
3
54
0
Order By: Relevance
“…Independent of housing conditions, socio-economic status was also associated with vector density; the poorer the household, the higher its exposure to sand flies. Similar associations were observed for other phlebotomine sand fly species in Panama [16]. In an earlier study in the same area in Bihar we were able to show statistically significant associations between housing conditions and socio economic status on one side and VL on the other [21].…”
Section: Discussionsupporting
confidence: 87%
“…Independent of housing conditions, socio-economic status was also associated with vector density; the poorer the household, the higher its exposure to sand flies. Similar associations were observed for other phlebotomine sand fly species in Panama [16]. In an earlier study in the same area in Bihar we were able to show statistically significant associations between housing conditions and socio economic status on one side and VL on the other [21].…”
Section: Discussionsupporting
confidence: 87%
“…infestation [24, 25]. Other risk factors such as destitute housing, which is inappropriate for residual insecticide application [26], and the rejection by the Gunas of different vector control measures, also contribute to the vulnerability of this region [22]. In fact, recent studies have shown that traditional house architecture found in Gunas communities is a risk factor for malaria transmission [23, 27].…”
Section: Discussionmentioning
confidence: 99%
“…10,11 One of the most widespread methods for sand fly control is indoor residual insecticide spraying [12][13][14] ; however, such measure becomes unsustainable over time, 15 and even after spraying, the characteristics, including floor, walls, and roof materials, and quality of the house could hamper sand fly control. 16,17 Some specific housing characteristics have been associated with various health problems, 7,18,19 including vectorborne diseases. 20,21 "Unhealthy" houses are more frequent in rural areas, were leishmaniasis is more frequent.…”
Section: Introductionmentioning
confidence: 99%